PROOF OF SOME INEQUALITIES - Isakova Markhabo Zinnatulloyevna (Bright Mind Publishing, 2025)
This article demonstrates simple methods for proving certain inequalities.
Keywords: Inequality, triangle, Heron's formula, quadratic mean.